PENGARUH PERILAKU KERJA DAN PELATIHAN TERHADAP KINERJA TIM REAKSI CEPAT BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA PARIAMAN - Sri Mulyani; Rifaldi Rifaldi (Ensiklopedia of Journal, 2019)
This study aims to determine the effect of work behavior and training on the performance of the Rapid Response Team of the Regional Disaster Management Agency (BPBD) of Kota Pariaman. Independent variables are work behavior (x1) and job training (x2). The dependent variable is Performance (Y). The sample in this study were 36 people. Data is collected using documentation and interviews. Data collection tools are questionnaires. Hypothesis testing using analysis, regression, t test, F test and determination. The results showed that there was an effect of work behavior on performance, t counted 2,381 with a significance value of 0,023. There is an effect of training on the performance of t count of 2.157 with a significance value of 0.038. This study provides information that the variable work behavior and job training on performance is 32.5%. This shows that employee performance is still influenced by other variables not examined in this study.